Molecular Structure Effects on Ionic Diode Performance in Desalination: Ultrahigh Rectification in Butylated Intrinsically Microporous Polyamine (PIM‐EA‐TB) - Zhongkai Li; Mariolino Carta; Neil B. McKeown; Raphael E. Agbenyeke; Jean‐Charles Eloi; David J. Fermin; Omotayo A. Arotiba; Frank Marken (ChemElectroChem, 2024)
Abstract Ionic diodes are components in ionic circuits for AC‐electricity driven desalination and ion extraction processes. Independent of the ionic diode type/mechanism, achieving ionic current rectification at high ionic strengths is challenging but important, for example in seawater desalination and treatment of brine. Here, the butylation of a molecularly rigid (glassy) polymer of intrinsic microporosity (PIM‐EA‐TB) is shown to give anionic diodes with ultrahigh rectification effects (associated with interfacial resistivity) even in high ionic strength aqueous 2 M NaCl solution. The effect is rationalised based on polymer structure affecting ion transport.